Bernstein's theoretical – empirical dialectic as a methodological basis for uncovering the social relations of pedagogic communication about family–school partnerships in the initial teacher education curriculum. Issue 2 (15th March 2023) - Williams, Keith
ABSTRACT: This paper demonstrates how the orientation of trainee teachers to messages relayed about an aspect of practice can be specified if a dialectic is kept between the theoretical and the empirical, in accordance with principles developed by Basil Bernstein. Bernstein's methodology has the capacity to establish subtle understandings of how practices are recognized by exposing the different constellations of social relations structuring modalities of pedagogic communication. Practices designed for use during initial teacher education (ITE) to encourage trainees to commit to development of family–school partnerships (FSP) are used to illustrate the utility of Bernstein's approach. The message ITE providers relay about FSPs has a direct bearing on trainees' knowledge, competences, values, and attitudes. How they recognize the legitimate message relayed has implications for their future practice. ITE providers should be concerned with identifying the social relations of pedagogic communication to determine whether a mode exists that will increase the likelihood of trainees adopting practices that make the establishment of FSPs more likely. The origins and originality of Bernstein's work is discussed and examples from research on FSPs are embedded into his methodology to illustrate how it serves as a framework with which to inform the design of ITE curricula.